PENGARUH KERAGAMAN PRODUK, KUALITAS PRODUK, DAN PROMOSI TERHADAP KEPUASAN KONSUMEN PADA RN DONUTS BAKERY DENGAN KEPUTUSAN PEMBELIAN SEBAGAI VARIABEL INTERVENING - Ningrum, Rafika Febri Pristika; Karnadi, Karnadi; Syahputra, Hendra (Fakultas Ekonomi dan Bisnis, 2024)
The purpose of this research is to determine the influence of product diversity, product quality, and promotion on consumer satisfaction at RN Donuts Bakery with purchasing decisions as an intervening variable. The population used in the research used all consumers at RN Donuts Bakery. The sampling technique uses simple random sampling technique. Data analysis and hypothesis testing in research uses Structural Equation Models - Partial Least Square (PLS-SEM). The results of the direct influence hypothesis test using the Smart PLS 3.0 application, show that product diversity has a significant positive effect on purchasing decisions, product diversity has a significant positive effect on consumer satisfaction, product quality has a significant positive effect on purchasing decisions, product quality has a positive but not significant effect on consumer satisfaction. , Promotion has a positive but not significant effect on purchasing decisions, Promotion has a positive but not significant effect on consumer satisfaction, Purchasing decisions have a significant positive effect on consumer satisfaction. The results of the indirect influence hypothesis test show that the product diversity variable has a positive but not significant effect on consumer satisfaction through purchasing decisions, product quality has a positive but not significant effect on consumer satisfaction through purchasing decisions, Promotion has a positive but not significant effect on consumer satisfaction through purchasing decisions.